Induccion hormonal de la lactancia durante la fase de cuerpo luteo en vaca infertil - Bermudez, del C.R.=700 1 Polanco, J.A.
(Es, En)
Ilus., 19 ref.
Keywords: VACA; LACTACION INDUCIDA; HORMONAS SEXUALES; ESTROGENOS; PROGESTERONA; CUERPO LUTEO; SINCRONIZACION; PROSTOGLANDINAS; MEXICO; REVISTA CHAPINGO